Traumatism during mooring operations on vessels - Shapovalov KA; Shapovalova PK (Annals of Marine Science - Peertechz Publications, 2020)
Introduction: Mooring operations on modern vessels remain one of the least mechanized types of work. Mooring injuries are characterized by a particularly gross violation of soft tissues and bones. Materials and methods: The analysis of the treatment of 224 patients from members of crew who received occupational injuries while mooring the vessels while performing voyages in the northern water basin. When working on the material, analytical and statistical methods were used. The significance of differences was calculated using Student's t-criteria for independent samples. Results: In the structure of occupational injuries of members of vessel`s crew of the Northern water basin, various injuries sustained during the mooring of vessels account for 10.1% of cases. In the Northern region, mooring injuries most often occur on transport river (46.7%) and sea (36.3%) ships, in which traffic is intensive, loading and unloading can occur at various berths within the same port, which increases the frequency of mooring operations during short transitions and, accordingly, the probability of mooring injuries. Outpatient treatment due to mooring injuries received 50.8% of members of vessel`s crew. The second half of the mooring injuries required emergency hospitalization, long-term treatment in the surgical department and further rehabilitation at the outpatient stage. Discussion: Every tenth work-related injury sustained by of members of vessel`s crew of the Northern water basin occurs during mooring operations. Compliance with the mooring technology of the vessel, the improvement of the materials from which the mooring ends are made and the development of automated mooring complexes are the main areas of technological reduction of mooring injuries. Preventive measures for the prevention of mooring injuries should be continuous systemic in nature and should concern not only the technical improvement of mooring mechanisms, but also the constant training of members of vessel`s crew in safety techniques, first aid in case of injuries and health education. Conclusions: 1. In the general structure of occupational traumatism of members of vessel`s crew of the Northern water basin, various damages during the mooring of vessels account for 10.1% of cases. 2. The risk of mooring injuries is greatest in the transport river and sea fleets among sailors with production experience of up to 1 year of work in the specialty. 3. Mooring injuries are characterized by the predominance of severe bruises, deep wounds and traumatic amputations of the phalanges of the fingers. 4. The average period of incapacity for work with mooring injuries is 48.0 working days, the hospital bed for hospitalization in the surgical department - 20.6. 5. Returned to professional work after rehabilitation for mooring injuries, 94.0% of the victims of members of vessel`s crew. The initial exit of victims to the II group of disability was 1.3%; Group III - 2.2%; 2.5% of mooring injuries were fatal.